Photodynamic therapy in pediatric age: Current applications and future trends - Di Bartolomeo, Luca; Altavilla, Domenica; Vaccaro, Mario; Vaccaro, Federico; Squadrito, Violetta; Squadrito, Francesco; Borgia, Francesco (Frontiers in Pharmacology, 2022)
Photodynamic therapy (PDT) is a photochemotherapy based on local application of a photosensitive compound and subsequent exposure to a light source of adequate wavelength. It is a non-invasive therapeutic procedure widely used in oncodermatology for treatment of numerous skin cancers, but in the last years its use has been gradually extended to an increasing list of skin diseases of both infectious and inflammatory nature. Although PDT is proven as a safe and effective therapeutic option in adults, its use is not well standardized in the pediatric population. In this review, we will focus on clinical applications, mechanisms of action, protocols, and adverse events in children and adolescents. Most of pediatric experiences concerned treatment of skin cancers in Gorlin syndrome and xeroderma pigmentosum, acne vulgaris, and viral warts, but other applications emerged, such as cutaneous lymphoma and pseudo-lymphomas, necrobiosis lipoidica, hidradenitis suppurativa, dissecting cellulitis, leishmaniasis, angiofibromas, verrucous epidermal nevus, and linear porokeratosis. In these pediatric diseases, PDT appeared as an effective therapeutic alternative. The results on vitiligo were limited and not fully encouraging. Although highly versatile, PDT is not a therapy for all skin diseases, and a deeper knowledge of its mechanisms of action is required to better define its spectrum of action and safety in pediatric patients.